2009
DOI: 10.1002/adfm.200900752
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Macroporous Microwell Array for Surface‐Enhanced Raman Scattering

Abstract: Here, a colloidal templating procedure for generating high‐density arrays of gold macroporous microwells, which act as discrete sites for surface‐enhanced Raman scattering (SERS), is reported. Development of such a novel array with discrete macroporous sites requires multiple fabrication steps. First, selective wet‐chemical etching of the distal face of a coherent optical fiber bundle produces a microwell array. The microwells are then selectively filled with a macroporous structure by electroless template syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…From the measured SERS enhancements, we can evaluate the role played by the gap size and density of Ag-NPs in different nanostructures. The Enhancement Factor (EF) 43,44 can be calculated quantitatively according to the following formula: [45][46][47] EF ¼ ðI SERS =N SERS Þ=ðI 0 =N 0 Þ; where I SERS and N SERS are the Raman peak intensity values and the total number of molecules adsorbed on the prepared substrate, and I 0 and N 0 are the corresponding parameters for the control sample (5 ll, 5 mM R6G solution deposited on a Si substrate in our experiment). This calculation is based on the fact that the intensity of the collected SERS signal is proportional to the total number of molecules if the molecules are at a low concentration level.…”
Section: Results and Discusionmentioning
confidence: 99%
“…From the measured SERS enhancements, we can evaluate the role played by the gap size and density of Ag-NPs in different nanostructures. The Enhancement Factor (EF) 43,44 can be calculated quantitatively according to the following formula: [45][46][47] EF ¼ ðI SERS =N SERS Þ=ðI 0 =N 0 Þ; where I SERS and N SERS are the Raman peak intensity values and the total number of molecules adsorbed on the prepared substrate, and I 0 and N 0 are the corresponding parameters for the control sample (5 ll, 5 mM R6G solution deposited on a Si substrate in our experiment). This calculation is based on the fact that the intensity of the collected SERS signal is proportional to the total number of molecules if the molecules are at a low concentration level.…”
Section: Results and Discusionmentioning
confidence: 99%
“…These simulations coupled with experimental results suggested that nanopore diameters of around 400 nm, the incorporation of the nanoparticle dimers within the first 10 μm beneath the surface, and keeping the light transmittance above 50% are all critical to achieve SERS substrates that show enhancement factors exceeding 10 10 for the selected benchmark Raman marker, benzenethiol (BT). The observed record enhancement factor is four orders of magnitude better than that commonly reported for this marker on 2D substrates of gold and silver nanostructures 48–50…”
mentioning
confidence: 57%
“…We used the CO stretching signal of R6G at 611 cm ¹1 as the characteristic peak (the strongest one in the range 5501800 cm ¹1 in this study) to calculate the EFs of the SERS sensitivity. We evaluated the EFs using the equation 19) EF…”
Section: Resultsmentioning
confidence: 99%